1988
DOI: 10.1007/bf01774069
|View full text |Cite
|
Sign up to set email alerts
|

Length and myofilament spacing-dependent changes in calcium sensitivity of skeletal fibres: effects of pH and ionic strength

Abstract: The calcium sensitivity of force was measured in glycerinated rabbit psoas fibres at sarcomere lengths (SL) from 2.3 to 3.4 micron. Increased SL caused calcium sensitivity to increase and the slope of force-calcium relations to decrease. We have hypothesized that length-dependent changes in myofilament lattice spacing and the presence of fixed charge on the myofilaments are important in determining calcium sensitivity. Lattice spacing changes were monitored by measuring fibre diameter (D). D was decreased by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
76
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 80 publications
12
76
2
Order By: Relevance
“…The groups of Moss et al (1983) and Stienen et al (1985) indicated that lattice spacing, rather than length, was responsible for the changes in Ca 2+ -sensitivity in membranepermeabilized skeletal muscles. These results were confirmed in skeletal (Godt and Maughan 1981;Wang and Fuchs 1995;Martyn and Gordon 1988) and cardiac (Wang and Fuchs 1995;McDonald and Moss 1995) muscle preparations which demonstrated that osmotic compression (as a function of muscle width) enhances Ca 2+ sensitivity. These findings were in agreement with the proposition of Hofmann and Fuchs (1987a, 1987a, 1987b who demonstrated that Ca 2+ -binding to cTnC directly regulates cross-bridges interactions (rather than sarcomere length).…”
Section: Interfilament Lattice Spacing Versus Myocyte Lengtheningsupporting
confidence: 53%
“…The groups of Moss et al (1983) and Stienen et al (1985) indicated that lattice spacing, rather than length, was responsible for the changes in Ca 2+ -sensitivity in membranepermeabilized skeletal muscles. These results were confirmed in skeletal (Godt and Maughan 1981;Wang and Fuchs 1995;Martyn and Gordon 1988) and cardiac (Wang and Fuchs 1995;McDonald and Moss 1995) muscle preparations which demonstrated that osmotic compression (as a function of muscle width) enhances Ca 2+ sensitivity. These findings were in agreement with the proposition of Hofmann and Fuchs (1987a, 1987a, 1987b who demonstrated that Ca 2+ -binding to cTnC directly regulates cross-bridges interactions (rather than sarcomere length).…”
Section: Interfilament Lattice Spacing Versus Myocyte Lengtheningsupporting
confidence: 53%
“…Single permeable rabbit skeletal muscle fibers or strips of permeable rabbit cardiac tissue were mounted between a sensitive force transducer and a fast motor, and isometric tension was measured as a function of Ca concentration, as described (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, endogenous TnC was extracted from the fibers, and the TnC-depleted fibers were reconstituted with an exogenous TnC to be tested. Force was measured on the reconstituted fibers as a function of free Ca 2ϩ concentration as described previously (Martyn and Gordon, 1988).…”
mentioning
confidence: 99%